Research group as helpers due to the war in Ukraine: Focus group experiences of women researchers - Roszik-Volovik, Xenia; Brandão, Anna Paula; Kollárovics, Nóra; Farkas, Bernadett Frida; Frank-Bozóki, Eszter; Horváth, Lili Olga; Kaló, Zsuzsa; Nguyen Luu, Lan Anh; Balazs, Judit (Frontiers in Psychiatry, 2023)
Introduction World Health Organization studies have shown that one in every five people who have experienced war or other conflicts suffers from a mental health disorder, the most vulnerable groups being children and women. According to international guidelines, mental health care should be made available immediately in the event of disaster. With the first influx of Ukrainian refugees to Hungary at the outbreak of the war, the Research Group of Childhood Mental Health at Eötvös Loránd University and Semmelweis University in Budapest immediately decided to help by transforming itself into a support group for refugee families. The members of the support group are all women. The aim of the present study is to explore the motivation behind the transformation of the research group and the help it provided. A further aim was to compare the group’s experiences with descriptions in the literature of impacts on helpers who work with refugees. Methods The current paper reflects on the transformation from researchers to helpers and the effects of that transformation at group and individual level using the focus group method and consensual text analysis. The transformation of the support group necessitated the involvement of students, whose experiences are also examined. Results We identified five main categories: context; the help recipients’ perspective; the personal level; the professional level; and the level between the personal and professional. Discussion The analysis revealed the way in which the voluntary helping developed, the resulting difficulties, and coping options. Volunteering among Ukrainian refugees has both positive and negative psychological consequences. While stress and trauma threaten the psychological well-being of the helpers, positive aspects, such as flexibility and professional development, are also reported. Due to the strong motivation among group members and their experience in practical work, the all female research group was quickly able to transform itself into a support group.